Heat Treatment Improves Hepatic Mitochondrial Respiratory Efficiency via Mitochondrial Remodeling. Issue 2 (22nd January 2021) - Von Schulze, Alex T; Deng, Fengyan; Fuller, Kelly N Z; Franczak, Edziu; Miller, Josh; Allen, Julie; McCoin, Colin S; Shankar, Kartik; Ding, Wen-Xing; Thyfault, John P; Geiger, Paige C
Abstract: Nonacholic fatty liver disease, or hepatic steatosis, is the most common liver disorder affecting the western world and currently has no pharmacologic cure. Thus, many investigations have focused on alternative strategies to treat or prevent hepatic steatosis. Our laboratory has shown that chronic heat treatment (HT) mitigates glucose intolerance, insulin resistance, and hepatic steatosis in rodent models of obesity. Here, we investigate the direct bioenergetic mechanism(s) surrounding the metabolic effects of HT on hepatic mitochondria. Utilizing mitochondrial proteomics and respiratory function assays, we show that one bout of acute HT (42°C for 20 min) in male C57Bl/6J mice ( n = 6/group) triggers a hepatic mitochondrial heat shock response resulting in acute reductions in respiratory capacity, degradation of key mitochondrial enzymes, and induction of mitophagy via mitochondrial ubiquitination. We also show that chronic bouts of HT and recurrent activation of the heat shock response enhances mitochondrial quality and respiratory function via compensatory adaptations in mitochondrial organization, gene expression, and transport even during 4 weeks of high-fat feeding ( n = 6/group). Finally, utilizing a liver-specific heat shock protein 72 (HSP72) knockout model, we are the first to show that HSP72, a protein putatively driving the HT metabolic response, does not play a significant role in the hepatic mitochondrial adaptation to acute or chronic HT. However, HSP72 is required for the reductions in blood glucose observed with chronic HT. Our data are the first to suggest that chronic HT (1) improves hepatic mitochondrial respiratory efficiency via mitochondrial remodeling and (2) reduces blood glucose in a hepatic HSP72-dependent manner. :